1997
DOI: 10.1128/jb.179.22.6880-6886.1997
|View full text |Cite
|
Sign up to set email alerts
|

katGI and katGII encode two different catalases-peroxidases in Mycobacterium fortuitum

Abstract: It has been suggested that catalase-peroxidase plays an important role in several aspects of mycobacterial metabolism and is a virulence factor in the main pathogenic mycobacteria. In this investigation, we studied genes encoding for this protein in the fast-growing opportunistic pathogen Mycobacterium fortuitum. Nucleotide sequences of two different catalase-peroxidase genes (katGI and katGII) of M. fortuitum are described. They show only 64% homology at the nucleotide level and 55% identity at the amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The highest amount of catalase-peroxidase per cell was observed when the cells were in the exponential phase of growth, which is consistent with the ¢nding that the lethal e¡ects of isoniazid lie in the mycolic acid biosynthetic pathway [6]. Similar to the M. tuberculosis T-catalase, which also has a peroxidase-like function, the catalase-peroxidase was heat-labile [5]. Similar to the recombinant catalaseperoxidase of M. tuberculosis [9], the puri¢ed enzyme corresponded to the catalase band and reacted with isoniazid and H P O P to produce radical products that could reduce NBT to a purple formazan product.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The highest amount of catalase-peroxidase per cell was observed when the cells were in the exponential phase of growth, which is consistent with the ¢nding that the lethal e¡ects of isoniazid lie in the mycolic acid biosynthetic pathway [6]. Similar to the M. tuberculosis T-catalase, which also has a peroxidase-like function, the catalase-peroxidase was heat-labile [5]. Similar to the recombinant catalaseperoxidase of M. tuberculosis [9], the puri¢ed enzyme corresponded to the catalase band and reacted with isoniazid and H P O P to produce radical products that could reduce NBT to a purple formazan product.…”
Section: Discussionsupporting
confidence: 66%
“…The recombinant catalase-peroxidase from M. tuberculosis [3] and a catalase-peroxidase from Mycobacterium smegmatis [4] have been puri¢ed. Menendez et al [5] suggested that to understand the role of this enzyme in drug activation and antibiotic resistance in pathogenic Mycobacterium spp., the characterization of catalase-peroxidases from other mycobacterial species with di¡erent susceptibilities to isoniazid was needed.…”
Section: Introductionmentioning
confidence: 99%
“…Various mycobacterial catalase-peroxidases (KatG) have been described: Menéndez et al [64] described the two catalase-peroxidases (KatG I and KatG II) produced by Mycobacterium fortuitum, Rafii et al [65] isolated and purified the catalase-peroxidase of a non-pathogenic fast-growing Mycobacterium sp. Pyr-1 and Ro et al [66] purified a catalase-peroxidase from Mycobacterium sp.…”
Section: Properties Of Catalase-peroxidasementioning
confidence: 99%
“…Mycobacteria display varied distribution of catalases among different species. Only HPI-type catalase-peroxidase is detected in Mycobacterium tuberculosis (KatG) (20) and Mycobacterium fortuitum (KatGI and KatGII) (29), whereas some species produce only HPII-type catalase and others produce both types (30,37). Research on mycobacterial catalases has been focused mainly on the role of KatG in conferring susceptibility to isoniazid (INH), an antituberculosis drug.…”
mentioning
confidence: 99%